Domain-Specific School Readiness among Sri Lanka Preschool Children: Evidence from the National ECDA: English - Thevarasa Mukunthan; Ranasinghe K.R.M.S (Postgraduate Program, University of Mataram, 2026)
School readiness is a multidimensional construct encompassing physical, social–emotional, cognitive, and language and early literacy development. Although overall readiness classifications are commonly used, they may mask domain-specific developmental vulnerabilities that influence children’s transition to formal schooling. This study examined patterns of school readiness among 360 Sri Lankan preschool children using the Early Childhood Development Assessment (ECDA), a standardized national tool assessing 22 indicators across four developmental domains. A quantitative descriptive cross-sectional design was employed, and descriptive statistical analysis (frequencies and percentages) was used to examine overall readiness levels and domain-specific developmental patterns. Results showed that 65.6% of children were classified as Level 1 (Good), while 34.4% required additional or intensive support (Levels 2 and 3). The most significant developmental vulnerabilities were observed in social–emotional development, early numeracy, spatial reasoning, and language and early literacy skills, particularly phonological awareness and information processing. Children in Level 3 exhibited substantial difficulties across all developmental domains. These findings highlight the importance of domain-sensitive assessment and targeted early interventions to address developmental gaps and support smoother transitions from preschool to primary education in Sri Lanka.